2013
DOI: 10.14260/jemds/413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Results of Bridge Plating in Comminuted Fractures of Long Bones

Abstract: Osteosynthesis with open reduction technique in comminuted fracture has several disadvantages like increase rate of non-union, soft tissue problem, infection and implant failure. These problems may be overcome by percutaneous bridge plating technique which preserve the vascularity and soft tissue attachment of fracture fragments. MATERIALS AND METHODS: Twenty-five patients were involve in this study. All of twentyfive patients with closed comminuted diaphyseal fractures of femur (n-10) and tibia (n-15) were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Andalib et al [5] reported 1 (2%) patient of non-union in series of 49 cases underwent MIPO for comminuted fractures of long bones. In the study conducted by Mandal et al [4] , 1 patient (4%) had non-union in 25 cases of comminuted fracture of long bones treated with MIPO. Limb length discrepancy of less than 2.5 cm was present in 2 (7.69%) patients that is not so significant.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Andalib et al [5] reported 1 (2%) patient of non-union in series of 49 cases underwent MIPO for comminuted fractures of long bones. In the study conducted by Mandal et al [4] , 1 patient (4%) had non-union in 25 cases of comminuted fracture of long bones treated with MIPO. Limb length discrepancy of less than 2.5 cm was present in 2 (7.69%) patients that is not so significant.…”
Section: Discussionmentioning
confidence: 96%
“…Early weight bearing resulted in implant failure. Mandal et al [4] reported 3 (12%) patients of restricted ROM in series of patient treated with MIPO in comminuted fracture of long bones. A total of 8 Postoperative complications were observed among the 26 patients followed up in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation